2020
DOI: 10.1016/j.rmed.2020.106206
|View full text |Cite
|
Sign up to set email alerts
|

Determining extent of COVID-19 pneumonia on CT based on biological variables

Abstract: Covid-19 pneumonia CT extent correlates well with outcome including mortality. However, CT is not widely available in many countries. This study aimed to explore the relationship between Covid-19 pneumonia CT extent and blood tests variations. The objective was to determine for the biological variables correlating with disease severity the cutoff values showing the best performance to predict the parenchymal extent of the pneumonia. Methods: Bivariate correlations were calculated between biological variables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
4
8
1
Order By: Relevance
“…This is in par with study done by Gupta P. et.al, [16] with average age of 54.1 years and 52 years in patient having severe and non-severe lung involvement respectively. Our study showed male predominance (Male 65%) which is similar to study by Tordjman M. et al, [9] which had a male predominance of 64.8% and study by Gupta P. et.al, [16] in his study in Indian population, found male predominance of 66.5%.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is in par with study done by Gupta P. et.al, [16] with average age of 54.1 years and 52 years in patient having severe and non-severe lung involvement respectively. Our study showed male predominance (Male 65%) which is similar to study by Tordjman M. et al, [9] which had a male predominance of 64.8% and study by Gupta P. et.al, [16] in his study in Indian population, found male predominance of 66.5%.…”
Section: Discussionsupporting
confidence: 90%
“…These results are also in correlation with studies published by, Tordjman M et.al. [9] Zhang J. et al [18] Orlacchio A et al [26] All these studies were supportive of significant positive correlation of CRP with CT severity score. Tordjman M. et al [9] also suggested that along with LDH, CRP can be used to predict parenchymal extent of the pneumonia.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…showed that there was a significant negative correlation between the degree of pulmonary inflammation on chest CT and the lymphocyte count (34). Another previous study from Tordjman et al reported moderate correlations between the severity of CT findings and the lymphocyte count in COVID-19 (35). In our study, more patients in the FC group had a decreased lymphocyte count level, leading to worse CT findings.…”
Section: Discussionsupporting
confidence: 50%